Prevalence of violence against older adults and associated factors in Çanakkale, Turkey: A cross‐sectional study. Issue 1 (10th December 2019) - Gürsoy, Melike Yalçın; Kara, Fatih
Abstract : Aim: This study was designed to determine the prevalence of domestic violence against older adults and the associated risk factors in Çanakkale, Turkey. Methods: A cross‐sectional, population‐based study was carried out, including 1230 individuals aged ≥65 years living in the city of Çanakkale, Turkey. The population of the study consisted of 73 367 individuals aged ≥65 years, living in Çanakkale. Sample selection was made with the one‐step cluster sampling method. The data were collected by face‐to‐face interview. The study was approved by the local ethics committee, and written consent was taken from the participants. Results: Of the participants, 4.1% had experienced physical violence, 2.5% were subjected to sexual abuse, 23.5% had undergone psychological violence and 12.2% had a history of economic violence. The exposure to any of the given violence types was 28.5%. Risk factors related to violence were being married, having children, educated partner, lack of economic independence, poor self‐perceived health, administration of medications by others, feeling lonely, dissatisfaction with life, poor perception of family relations and not participating in family decisions. Conclusions: These results show that violence against older adults is a significant problem in a city in western Turkey. Therefore, an in‐depth evaluation of the determined risk factors related to violence and actions for its prevention are warranted. Geriatr Gerontol Int 2020; 20: 66–71 .